New locality record of crab-eating mongoose Herpestes urva (Hodgson, 1836) from Parbat District of Nepal - Bhusal, Arjun; Baral, Badri; Chhetri, Sumana; Pradhan, Aavas; Bist, Bhuwan Singh; Pangeni, Mandip; Poudel, Santosh (Nepalese Journal of Zoology, 2022)
Crab-eating mongoose Herpestes urva is one of the least studied small mammal species of Nepal with very few confirmed locality records. This paper presents the new location of crab-eating mongoose from agricultural land adjacent to the Schima-Castanopsis-dominated forest habitat of Parbat District in Gandaki Province, Nepal. Three individuals of crab-eating mongoose were sighted and photographed at an altitude of 1,515 m on swampy agricultural land at the edge of a fragmented forest patch of Schima-Castanopsis-dominated forest in Arthar Village of Kushma Municipality.